This is service design thinking : basics - tools - cases. - Schneider, Jakob, ....-; Stickdorn, Marc, ....- (Amsterdam : Bis, 2011)
Service design thinking is the designing and marketing of services that improve the customer experience, and the interactions between the service providers and the customers. If you have two coffee shops right next to each other, and each sell the exact same coffee at the exact same price, service design is what makes you walk into one and not the other. Maybe one plays music and the other doesn't. Maybe one takes credit cards and the other is cash only. Maybe you like the layout of one over the other, or one has more comfortable seating. Maybe the staff at one is friendlier, or draws fun shapes on the top of their lattes. All of these nuances relate to service design. This Is Service Design Thinking combines the knowledge of twenty-three international authors and even more online contributors from the global service design community and is divided into three sections: Basics: outlines service design thinking along five basic principles Tools: describing a variety of tools and methods used in Service Design Thinking Cases: vivid examples for the introduced fundamentals with real-life case studies from 5 companies that did inspiring projects within the field of Service Design At the end, a one-page 'Customer Journey Canvas' is included, which can be used to quickly sketch any service on a single sheet of paper-capturing different stakeholder concerns: e.g. customers, front-line staff and management.